Spiritual Commitment of Educational Leadership as a Loyalty in Human Resources Management: The Javanese Concept of Kekeluargaan - Wiryadinata, Halim; Nadeak, Bernadetha (International Journal of Educational Management and Innovation, 2025)
This research aims to show that the Javanese concept of Kekeluargaan as the spiritual commitment influences the loyalty of human resources through management. Human loyalty depends upon fulfilling employees’ needs, which is one of the motivation factors for working. The meaning of work becomes absurd and leads to the material element as the form of human resources development. This old-fashioned paradigm cannot perform the best human resources performance due to commitment and spiritual factors. The previous element creates the incapability of humans to search for the meaning of work for life. The latter makes humans unable to appreciate the job for themselves. Therefore, human resources development issues become a burden for organizations.  The method uses the sociological approach to evaluate and analyze the emic through books, articles, journals, and academic writings to systematize research division through analytical thinking. The result is that the concept of Kekeluargaan, as an Indonesian local culture, becomes a spiritual commitment to bringing diversity to the organization as one family. The conclusion is that the valuable points of Kekeluargaan create a workplace atmosphere for human resources that is happy, comfortable, involved, and together in line with spiritual values.